SOFT START DEVISE INTRODUCTION AS A WAY TO ENERGY EFFICIENCY OF THE ENTERPRISE - Федорів, Михайло (Modern engineering and innovative technologies, 2023)
The article discusses ways of saving in electrotechnical oil and gas complexes. An analysis of the introduction of soft start devices for asynchronous motors of pumping units and their functioning in different modes of operation was carried out. The propo